Memory, Neuroscience and Memory Enhancement - Alonso Fernández, Marcos (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2020)
This paper advances a new and updated understanding of memory that should also change the coordinates of the memory enhancement debate. Instead of thinking of memory as a storehouse, we should think of memory from a narrative perspective. This view allows for a better understanding of the process in which we actually construct our memories by elaborating meaningful summaries, rather than adding discrete elements. I argue that this new way of thinking about memory makes most of the memory enhancement technologies we have or will have in the near future much less ethically problematic. The main idea is that (biological) memory interacts with memory enhancement in the creative and re-elaborative way it ordinarily does. To conclude, I discuss some cases to illustrate the previous points.